A silicon-carbon composite negative electrode material and preparation method thereof

Through the composite of silicon nanomaterials and carbon materials and the coating granulation and carbonization of liquid asphalt, silicon carbon composite materials with excellent performance were prepared, which solved the problem of volume expansion and insufficient conductivity of silicon-based negative electrode materials, and achieved high cycling stability and high energy density.

CN119742352APending Publication Date: 2025-04-01SHENZHEN JINTANG NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411984297.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have volume expansion effects and unstable electrode electrolyte interfaces in lithium-ion batteries, limiting their cyclic stability and energy density.

Method used

Silicon-carbon composite material with a special structure was prepared by initially mixing the silicon nanomaterial with the carbon material, then mixing it with liquid asphalt and ball milling again, and finally carbonizing in an inert atmosphere.

Benefits of technology

This method not only buffers the expansion of silicon during the lithiation process, improves the conductivity, but also significantly improves the cycle stability and rate performance of silicon-carbon composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742352A_ABST
    Figure CN119742352A_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-carbon composite negative electrode material and a preparation method thereof, wherein the preparation method comprises the following steps: S1, mixing and grinding silicon nanomaterials and carbon materials in a specific mass ratio, and then putting them into a ball mill to obtain a silicon-carbon mixed product after ball milling; S2, mixing the silicon-carbon ground mixed product and asphalt material in a specific mass ratio, and then putting them into a ball mill to obtain a silicon-carbon precursor after ball milling; S3, carbonizing the silicon-carbon precursor under the protection of an inert atmosphere to obtain a silicon-carbon composite negative electrode material. The present invention combines the advantages of silicon and carbon materials, and uses liquid asphalt for coating granulation and carbonization treatment. The carbon component can effectively buffer the expansion of silicon during the lithiation process and make up for its insufficient conductivity; the asphalt carbon coating significantly reduces the surface activity and specific surface area of ​​the material, thereby improving the first cycle efficiency and cycle stability; when used as a negative electrode material for lithium-ion batteries, it exhibits excellent cycle performance and high rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-carbon composite negative electrode material and a preparation method thereof. Background Art

[0002] There is a huge market demand for high-energy-density lithium-ion batteries, and high-capacity electrode materials are the key to improving battery energy density. Among the negative electrode materials for lithium-ion batteries, graphite is currently the material that has been commercially applied on a large scale, but the specific capacity of graphite is close to its theoretical specific capacity limit (372mAh g -1 ), it is extremely difficult to further increase the capacity. However, the theoretical specific capacity of silicon-based negative electrode materials is much higher than that of graphite (4200mA hg -1 ), suitable working voltage, environmental friendliness, non-toxicity, high natural abundance and other characteristics, making it the most promising new lithium-ion battery negative electrode material on the market. However, severe volume expansion effect and unstable electrode-electrolyte interface are severe challenges facing the development of silicon materials.

[0003] Composite silicon materials with carbon is an effective strategy to solve the poor cycle stability and insufficient conductivity of silicon negative electrode materials. In particular, the preparation of carbon-coated silicon composite materials can buffer the volume expansion of silicon and improve the conductivity of electrode materials. At present, there are two main structures of carbon-coated silicon particles: core-shell structure and yolk-eggshell structure. Core-shell silicon-carbon composite materials refer to a silicon-carbon composite material in which a solid silicon core is completely covered with a conductive carbon shell. However, in some cases, this advantage is limited because the volume of the internal silicon core changes greatly during the lithiation process, which still inevitably leads to the volume expansion of the entire core-shell composite material [Jiang Bolun, et al. Dual Core-Shell Structured Si@SiOx@CNanocomposite Synthesized via a One-Step Pyrolysis Method as a Highly Stable Anode Material for Lithium-Ion Batteries[J]. ACS Applied Materials&Interfaces,. 2016, 8, 31611-31616.]. The yolk-eggshell structure is a composite material formed by adding a gap between the silicon core and the carbon shell. The yolk-eggshell structure can significantly improve the cyclic stability of silicon-based negative electrode materials under low area mass load, but its inherent large specific surface area and hollow space will inevitably reduce the volume density, thereby reducing its volume energy, limiting its practical application in lithium-ion batteries [Hu Le, et al.Yolk-shell Si / C composites with multiple Si nanoparticles encapsulated into double carbon shells as lithium-ion battery anodes [J]. Journal of Energy Chemistry, 2019, 32, 124-130.]. CN112186181A discloses a method of preparing a carbon source material, silicon particles, and a solvent into a reaction mixture, adding the reaction mixture dropwise to an emulsifying dispersant, coating the carbon source material with silicon particles, and finally subjecting the silicon-carbon source composite material to high-temperature carbonization to obtain a silicon-carbon composite material. However, the process flow of this method is long and the process is complicated, and only carbon-coated silicon particles are finally formed, lacking the reserved space for buffering the volume expansion of silicon. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a silicon-carbon composite negative electrode material and a preparation method thereof, wherein silicon and carbon materials are composited, and liquid asphalt is introduced for coating granulation and carbonization treatment, thereby obtaining a silicon-carbon composite material with a special structure. This unique structure not only provides a buffer zone for the expansion of silicon during the lithiation process, but also makes up for the poor electrical conductivity of silicon, and the tap density of the silicon-carbon negative electrode material can be effectively improved through ball milling granulation.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0007] S1. Preliminarily mix the silicon nanomaterial and the carbon material according to a specific mass ratio, put them into a ball mill, and obtain a silicon-carbon mixed product after ball milling;

[0008] S2, preliminarily mixing the silicon-carbon grinding mixture and the asphalt material according to a specific mass ratio, putting them into a ball mill, and obtaining a silicon-carbon precursor after ball milling;

[0009] S3. Carbonizing the silicon-carbon precursor under the protection of an inert atmosphere to obtain a silicon-carbon composite negative electrode material.

[0010] The silicon nanomaterial added in step S1 is nanoparticles with a particle size between 30-150 nm, or silicon nanosheets with a thickness of 10-100 nm and a width of less than 10 μm.

[0011] The carbon material added in step S1 is one or more of granular activated carbon, powdered coke, carbon black, carbon nanotubes, and graphene.

[0012] The mass ratio between the silicon nanomaterial and the carbon material added in step S1 is 1:(0.2-2).

[0013] In the step S1, the ball milling speed is 100-300 rpm, and the ball milling time is 5-20 min.

[0014] The asphalt material added in step S2 is one or more of medium-temperature coal asphalt, high-temperature coal asphalt, mesophase asphalt, and petroleum asphalt.

[0015] The mass ratio between the silicon-carbon grinding mixture added in step S2 and the asphalt material is 1:(0.1-1).

[0016] In step S2, the ball milling speed is 100-300 rpm, and the ball milling time is 5-20 min.

[0017] In step S1, the ratio of granular silicon nanomaterials to carbon materials should be appropriate. If the amount of carbon material added is too little, it cannot buffer the volume expansion of silicon well, making the cycle stability worse; if the amount of carbon material added is too large, due to its own high surface area and surface activity and low reversible capacity, it will reduce the first cycle efficiency and reversible capacity of the silicon-carbon negative electrode.

[0018] The amount of asphalt added in step S2 also needs to be precisely controlled. If the amount of asphalt is too large, although the coating structure can be more perfect, the content of active silicon in the silicon-carbon composite material is relatively reduced, making the capacity lower; if the amount of asphalt is too small, the silicon / carbon material cannot be well coated, and the performance of the first effect, circulation, etc. will be deteriorated.

[0019] Preferably, the ball milling adopts a planetary ball mill.

[0020] The inert atmosphere in step S3 is argon or nitrogen.

[0021] The conditions for the carbonization treatment in step S3 are: carbonization temperature of 700-900° C., carbonization time of 0.5-3 h, and heating rate of 2-10° C. / min.

[0022] A silicon-carbon composite negative electrode material obtained according to the above preparation method.

[0023] An application of the silicon-carbon composite negative electrode material obtained according to the above preparation method as a negative electrode material for a lithium ion battery.

[0024] The technical solution of the present invention has the following advantages:

[0025] A. Through special structural design, the present invention successfully combines the advantages of silicon and carbon materials, and uses liquid asphalt for coating, granulation and carbonization treatment to prepare a silicon-carbon composite material with excellent performance. The carbon component in this material has high flexibility, small particles, good dispersibility and excellent conductivity, which can effectively buffer the expansion of silicon during the lithiation process and make up for the insufficient conductivity of silicon materials. At the same time, the asphalt carbon coating significantly reduces the surface activity and specific surface area of ​​the material, thereby improving the first cycle efficiency and cycle stability. This makes the composite material exhibit excellent cycle performance and high rate performance when used as a negative electrode material for lithium-ion batteries.

[0026] B. The present invention proposes a simple, efficient and environmentally friendly method for preparing silicon-carbon negative electrode materials. This method not only simplifies the preparation process and shortens the preparation cycle, but also the materials used in the whole process are green, non-toxic and environmentally friendly. By cleverly using carbon materials with poor mechanical properties to provide a buffer zone for the expansion of silicon particles, and combining asphalt granulation technology, a coating layer with excellent mechanical properties is formed on the outermost layer, which effectively inhibits the expansion of silicon particles. In addition, the silicon-carbon composite material prepared by a ball mill has a higher tap density, which in turn improves the energy density of the battery and significantly improves the battery's rate performance and cycle stability. This preparation method not only has practical application value, but also provides a new idea for the green and efficient preparation of negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a SEM image of the silicon-carbon composite negative electrode material obtained in Example 1;

[0029] Figure 2 The silicon-carbon negative electrode obtained in Example 1 and Comparative Example 1 is 0.5A g -1 Cycling performance diagram under current density;

[0030] Figure 3 This is a rate curve diagram of the silicon-carbon negative electrode obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0034] S1. Weigh 0.4 g of silicon particles (D50 = 100 nm) and 0.2 g of acetylene black, mix them, put them into a ball mill, and after ball milling for 10 min, take out the product to obtain a silicon-carbon mixed product;

[0035] S2, weigh 0.2g of high temperature coal tar pitch (softening point 115°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 20 minutes to obtain a silicon-carbon precursor;

[0036] S3, the silicon-carbon precursor is heated to 800 degrees at 10 degrees / min in an argon atmosphere and kept at this temperature for 2 hours to obtain a silicon-carbon composite negative electrode material. Its morphology and electrochemical properties are shown in Figure 1-3 When used as a negative electrode material for lithium-ion batteries, it has a reversible specific capacity of 1700 mAh / g at a current density of 1 A / g, and the capacity retention rate remains at 80% after 200 cycles.

[0037] Example 2

[0038] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0039] S1. Weigh 0.4 g of silicon particles (D50 = 30 nm) and 0.4 g of YP50-F activated carbon, mix them, put them into a ball mill, and after ball milling for 10 minutes, take out the product to obtain a silicon-carbon mixed product;

[0040] S2, weigh 0.2g of medium-temperature coal tar pitch (softening point 73°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 15 minutes to obtain a silicon-carbon precursor;

[0041] S3, the silicon-carbon precursor was heated to 900 degrees at 5 degrees Celsius / min in an argon atmosphere and kept at that temperature for 1 hour to carbonize, thereby obtaining a silicon-carbon composite negative electrode material with a reversible capacity of 1650 mAh / g.

[0042] Example 3

[0043] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0044] S1. Weigh 0.4 g of silicon particles (D50 = 50 nm) and 0.4 g of coke powder (particle size 1-10 μm), mix them, put them into a ball mill, and after ball milling for 20 minutes, take out the product to obtain a silicon-carbon mixed product;

[0045] S2, weigh 0.08g of mesophase pitch (softening point 270°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 15 minutes to obtain a silicon-carbon precursor;

[0046] S3, the silicon-carbon precursor was heated to 900 degrees at 8 degrees / min in an argon atmosphere and kept at this temperature for 1 hour to obtain a silicon-carbon composite negative electrode material with a reversible lithium storage capacity of 1560 mAh / g.

[0047] Example 4

[0048] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0049] S1. Weigh 0.4 g of silicon particles (D50 = 100 nm) and 0.2 g of YP80-F activated carbon, mix them, put them into a ball mill, and after ball milling for 10 min, take out the product to obtain a silicon-carbon mixed product;

[0050] S2, weigh 0.2g of high temperature coal tar pitch (softening point 115°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 10 minutes to obtain a silicon-carbon precursor;

[0051] S3, the silicon-carbon precursor is heated to 800 degrees at 10 degrees / min in an argon atmosphere and kept at this temperature for 3 hours to carbonize, thereby obtaining a silicon-carbon composite negative electrode material with a reversible lithium storage capacity of 1460 mAh / g.

[0052] Example 5

[0053] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0054] S1. Weigh 0.4 g of silicon particles (D50 = 150 nm) and 0.8 g of YP50-F activated carbon, mix them, put them into a ball mill, and after ball milling for 10 minutes, take out the product to obtain a silicon-carbon mixed product;

[0055] S2, weigh 1.2g of medium-temperature coal tar pitch (softening point 73°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 10 minutes to obtain a silicon-carbon precursor;

[0056] S3, the silicon-carbon precursor was heated to 900 degrees at 10 degrees Celsius / min in an argon atmosphere and kept at that temperature for 0.5 hours to obtain a silicon-carbon composite negative electrode material with a reversible capacity of 1550 mAh / g.

[0057] Example 6

[0058] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0059] S1. Weigh 0.4 g of silicon particles (D50 = 100 nm) and 0.4 g of multi-walled carbon nanotubes, mix them, put them into a ball mill, and after ball milling for 5 minutes, take out the product to obtain a silicon-carbon mixed product;

[0060] S2, weigh 0.2g of high temperature coal tar pitch (softening point 115°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 10 minutes to obtain a silicon-carbon precursor;

[0061] S3, the silicon-carbon precursor was heated to 800 degrees at 10 degrees / min in an argon atmosphere and kept at that temperature for 2 hours to carbonize, thereby obtaining a silicon-carbon composite negative electrode material with a reversible capacity of 1550 mAh / g.

[0062] Example 7

[0063] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0064] S1. Weigh 0.4 g of silicon particles (D50 = 50 nm) and 0.1 g of graphene (5-10 layers), mix them, put them into a ball mill, and after ball milling for 20 min, take out the product to obtain a silicon-carbon mixed product;

[0065] S2, weigh 0.2g of medium-temperature coal tar pitch (softening point 73°C) and mix it with the silicon-carbon mixed product, then put it into a ball mill, and ball mill for 15 minutes to obtain a silicon-carbon precursor;

[0066] S3, the silicon-carbon precursor was heated to 900 degrees at 5 degrees Celsius / min in an argon atmosphere and kept at this temperature for 2 hours to obtain a silicon-carbon composite negative electrode material with a reversible capacity of 1670 mAh / g.

[0067] Example 8

[0068] This embodiment provides a silicon-carbon composite negative electrode material, and the preparation method thereof comprises the following steps:

[0069] S1. Weigh 0.4 g of silicon nanosheets (thickness of about 50 nm, width of 500 nm) and 0.08 g of superconducting carbon black, mix them, put them into a ball mill, and after ball milling for 5 min, take out the product to obtain a silicon-carbon mixed product;

[0070] S2, weigh 0.2g of petroleum asphalt and silicon-carbon mixed product, put them into a ball mill, and ball mill for 5min to obtain silicon-carbon precursor;

[0071] S3, the silicon-carbon precursor was heated to 700 degrees at 2 degrees Celsius / min in an argon atmosphere and kept at that temperature for 1 hour to carbonize, thereby obtaining a silicon-carbon composite negative electrode material with a reversible capacity of 1580 mAh / g.

[0072] Comparative Example 1

[0073] This comparative example provides a silicon-carbon negative electrode material, and its preparation method comprises the following steps:

[0074] S1. Weigh 0.4 g of silicon particles (D50 = 100 nm) and 0.2 g of acetylene black, mix them, put them into a ball mill, and after ball milling for 10 min, take out the product to obtain a silicon-carbon mixed product;

[0075] S2. The silicon-carbon mixed product is heated to 800 degrees at a rate of 10 degrees Celsius / min in an argon atmosphere and kept at this temperature for 2 hours to carbonize to obtain a silicon-carbon negative electrode material.

[0076] Figure 2 The cycle performance comparison of the silicon-carbon negative electrode material prepared in Example 1 and the silicon-carbon negative electrode material in Comparative Example 1 is shown. The first five cycles were formed using a small current of 0.1A / g, and then a large current of 1A / g was used for the cycle test. It was found that in Comparative Example 1, since only acetylene black was mixed, the silicon content in its composite material was higher than the cycle capacity of the first few cycles in Example 1 in which both acetylene black and coated asphalt were added, but due to the lack of asphalt carbon coating, its cycle stability was poor, retaining only about 500mAh / g of specific capacity after 200 cycles, while the silicon-carbon negative electrode material prepared in Example 1 still maintained a high specific capacity of about 1100mAh / g after 200 cycles. Figure 3 The rate performance comparison of the materials at different current densities is given. Similarly, the silicon-carbon negative electrode material of Example 1 shows higher reversible capacity and cycle stability than the silicon-carbon material of Comparative Example 1 at different current densities. The reason is that the presence of the outer layer of asphalt carbon coating suppresses the volume change of the inner core silicon-carbon negative electrode material during the charge and discharge process, maintains the particle integrity of the negative electrode material, and achieves stable charge and discharge under long cycle and high current conditions.

[0077] Through special structural design, the present invention successfully combines the advantages of silicon and carbon materials, and uses liquid asphalt for coating, granulation and carbonization treatment to prepare a silicon-carbon composite material with excellent performance. The carbon component in the material has high flexibility, small particles, good dispersibility and excellent conductivity, which can effectively buffer the expansion of silicon during the lithiation process and make up for its insufficient conductivity. At the same time, the asphalt carbon coating significantly reduces the surface activity and specific surface area of ​​the material, thereby improving the first cycle efficiency and cycle stability. This allows the composite material to exhibit excellent cycle performance and high rate performance when used as a negative electrode material for lithium-ion batteries.

[0078] The present invention proposes a simple, efficient and environmentally friendly method for preparing silicon-carbon negative electrode materials. This method not only simplifies the preparation process and shortens the preparation cycle, but also the materials used in the whole process are green, non-toxic and environmentally friendly. By cleverly using carbon materials with poor mechanical properties to provide a buffer zone for the expansion of silicon particles, and combining asphalt granulation technology, a coating layer with excellent mechanical properties is formed on the outermost layer, which effectively inhibits the expansion of silicon particles. In addition, the silicon-carbon composite material prepared by a ball mill has a higher tap density, thereby improving the energy density of the battery, and significantly improving the battery's rate performance and cycle stability. This preparation method not only has practical application value, but also provides a new idea for the green and efficient preparation of negative electrode materials for lithium-ion batteries.

[0079] Any matters not described in the present invention are applicable to the prior art.

[0080] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon composite negative electrode material, characterized in that: The steps include: S1, mixing silicon nanomaterials and carbon materials in a certain mass ratio, putting them into a ball mill, and obtaining a silicon-carbon mixed product after ball milling; S2, mixing the silicon-carbon mixed product in step S1 and the asphalt material according to a certain mass ratio, putting them into a ball mill, and obtaining a silicon-carbon precursor after ball milling; S3. Carbonizing the silicon-carbon precursor under the protection of an inert atmosphere to obtain a silicon-carbon composite negative electrode material.

2. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: The silicon nanomaterial added in step S1 is nanoparticles with a particle size between 30-150 nm, or silicon nanosheets with a thickness of 10-100 nm and a width of less than 10 μm.

3. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: The carbon material added in step S1 is one or more of granular activated carbon, powdered coke, carbon black, carbon nanotubes, and graphene.

4. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: The mass ratio between the silicon nanomaterial and the carbon material added in step S1 is 1:(0.2-2).

5. The method for preparing the silicon-carbon composite negative electrode material according to claim 1, characterized in that: The asphalt material added in step S2 is one or more of medium-temperature coal asphalt, high-temperature coal asphalt, mesophase asphalt, and petroleum asphalt.

6. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: The mass ratio between the silicon-carbon grinding mixture added in step S2 and the asphalt material is 1:(0.1-1).

7. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: In the step S1, the ball milling speed is 100-300 rpm, and the ball milling time is 5-20 min; in the step S2, the ball milling speed is 100-300 rpm, and the ball milling time is 5-20 min.

8. The method for preparing a silicon-carbon composite negative electrode material according to claim 1, characterized in that: In step S3, the inert atmosphere is argon or nitrogen; the conditions for carbonization treatment are: carbonization temperature 700-900°C, carbonization time 0.5-3h, and heating rate 2-10°C / min.

9. A silicon-carbon composite negative electrode material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the silicon-carbon composite negative electrode material obtained by the preparation method according to any one of claims 1 to 8 as a negative electrode material for lithium-ion batteries.

Citation Information

Patent Citations

  • Silicon-carbon composite material and preparation method thereof, lithium battery negative electrode and lithium battery

    CN112186181A